Incorporating mixed cations in quasi-2D perovskites for high-performance and flexible photodetectors. Issue 6 (25th July 2019) - Dong, Ruoting; Lan, Changyong; Li, Fangzhou; Yip, SenPo; Ho, Johnny C.
Abstract : A simple method is developed to incorporate formamidinium and Cs mixed cations into quasi-2D perovskites of (iBA)2 (CH3 NH2 )3 Pb4 I13 (iBA = iso-butylamine) to enhance their film qualities and improve their subsequently fabricated device performances. Abstract : Recently, due to the excellent and tunable optoelectrical properties, quasi-two-dimensional (quasi-2D) layered perovskites have attracted tremendous attention for next-generation optoelectronic devices. However, fabricating high-quality 2D perovskite films, especially with low trap density, is still a challenge. Here, we successfully incorporate different concentrations of FA and Cs cations ( i.e. mixed cations) into the quasi-2D perovskites of (iBA)2 (MA)3 Pb4 I13 (FA = formamidinium; iBA = iso-butylamine; MA = methylamine) to modulate their thin film qualities, improving their subsequently fabricated device performances. When configured into photodetectors on rigid substrates, the optimal mixed cation-incorporated (iBA)2 (MA)3 Pb4 I13 perovskites exhibit impressive photodetection properties, which are comparable or even better than those of other 2D perovskite-based photodetectors previously reported. Once fabricated as a flexible photodetector on polyimide, the quasi-2D perovskite device demonstrates further improved performances, yielding a good responsivity of 400 mA W −1, a high detectivity up to 1.68 × 10 12 Jones and fast response speeds (rise and decay time constants of 43 and 22 ms, respectively) under 532 nm illumination. Importantly, the obtained devices possess excellent mechanical flexibility and durability with photocurrent maintaining 82% of the initial value even after 9000 bending cycles. This work can provide valuable design guidelines of 2D perovskites to obtain high-performance flexible photodetectors for next-generation optoelectronics.